Continuous thermosalinograph oceanography along RV SONNE cruise track SO307 - Michael Schlundt; Denise Pöhnl; Benjamin Pontiller; Jörg Geldmacher (PANGAEA, 2025)
Underway temperature and salinity data was collected along the cruise track with two autonomous measurement systems, called self-cleaning monitoring boxes (SMBs). Usually, the SMBs are changed after ~12 hours. While temperature is taken at the water inlet in about 4 m depth, salinity is estimated within the SMB from conductivity and interior temperature. No temperature calibration was performed. Salinity was calibrated against discrete water samples taken from the seawater inlet in 4 m depth. For details to all processing steps see Data Processing Report.